2022
DOI: 10.3390/antibiotics11081088
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Options and Outcomes for the Treatment of Neonates and Preterms with Gram-Negative Multidrug-Resistant Bacteria: A Systematic Review

Abstract: Background: Infections caused by multidrug-resistant (MDR) or extensively drug-resistant (XDR) bacteria represent a challenge in the neonatal population due to disease severity and limited therapeutic possibilities compared to adults. The spread of antimicrobial resistance and drug availability differ significantly worldwide. The incidence of MDR bacteria has constantly risen, causing an increase in morbidity, mortality, and healthcare costs in both high-income (HIC) and low- and middle-income countries (LMIC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…According to a recent systematic review aiming to identify the current antimicrobial treatment options for MDR and XDR GNB infections in the neonatal population, colistin in combination with meropenem, amikacin, ciprofloxacin, or tigecycline is used for CRE neonatal infections, whereas, in association with other antimicrobials such as ciprofloxacin, it is prescribed for DTR and XDR P. aeruginosa. Furthermore, the most active antimicrobial for XDR A. baumannii seems to be colistin, whereas novel antimicrobials such as ceftazidime–avibactam are infrequently used as salvage therapy [ 21 ]. Novel antimicrobials seem to be promising based on experience from studies in adults and lately from a very small but increasing number of trials including neonates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a recent systematic review aiming to identify the current antimicrobial treatment options for MDR and XDR GNB infections in the neonatal population, colistin in combination with meropenem, amikacin, ciprofloxacin, or tigecycline is used for CRE neonatal infections, whereas, in association with other antimicrobials such as ciprofloxacin, it is prescribed for DTR and XDR P. aeruginosa. Furthermore, the most active antimicrobial for XDR A. baumannii seems to be colistin, whereas novel antimicrobials such as ceftazidime–avibactam are infrequently used as salvage therapy [ 21 ]. Novel antimicrobials seem to be promising based on experience from studies in adults and lately from a very small but increasing number of trials including neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, the above guidance reports are not addressed to neonates. According to recent systematic reviews about therapeutic options in neonates, the limited number of published articles, the low quality of evidence (retrospective data, heterogenous study design, and outcome definition, case series, or reports), and the very small sample size not permitting any statistical analysis further suggest that neonates remain “therapeutic orphans” in the fight against AMR [ 17 , 21 ]. A lack of evidence regarding pharmacokinetics (PK), safety, route (continuous or intermittent), dose and duration of administration, and the guidelines of using specific antibiotic(s) are the causes of the common off-label/unlicensed antibiotic use in neonates [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Colistin in combination with other antimicrobials such as meropenem, amikacin, ciprofloxacin, or tigecycline were used for carbapenem-resistant Enterobacterales infections, whereas colistin plus ciprofloxacin were prescribed for difficult-to-treat resistant and extensively drug-resistant P. aeruginosa. Authors concluded the following: (a) in the last two decades, colistin is the most frequently studied and used antimicrobial, especially in low -middle income countries, with variable evidence of efficacy; (b) carbapenems are still the leading antibiotics for extended-spectrum beta-lactamase Enterobacterales; and (c) newer antibiotics, such as beta-lactam agents / beta-lactamase inhibitor combination (e.g., ceftazidime-avibactam infrequently used as salvage therapy), are promising, but data are few and limited to high income countries [43,44]. Indications, dosing regimens, and side effects of antibacterial agents are summarized in Table 1, while more details are presented in the Supplementary Table S1 [25,31,36,[44][45][46][47][48][49][50].…”
Section: Antimicrobial Agentsmentioning
confidence: 99%
“…To date, treatment options for MDR organisms in NICU are alarmingly limited [ 38 , 39 , 40 ], particularly for Gram-negative strains. Colistin is the main used antimicrobial for the treatment of MDR P. aeruginosa, A. baumannii, and CRE in newborns in the two last decades, with 75–100% of clinical success [ 41 ]. Meropenem at high doses or as an extended infusion or in association with other antimicrobials is the second most reported agent [ 40 , 41 ], while the use of tigecycline, fluoroquinolones, and polymyxin B is less frequently documented [ 24 , 40 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Colistin is the main used antimicrobial for the treatment of MDR P. aeruginosa, A. baumannii, and CRE in newborns in the two last decades, with 75–100% of clinical success [ 41 ]. Meropenem at high doses or as an extended infusion or in association with other antimicrobials is the second most reported agent [ 40 , 41 ], while the use of tigecycline, fluoroquinolones, and polymyxin B is less frequently documented [ 24 , 40 , 42 , 43 ]. However, the polymyxins safety profile is not optimal, as nephrotoxicity has been reported in newborns in 10–19% of cases [ 42 ] along with significant electrolyte imbalances [ 42 ].…”
Section: Introductionmentioning
confidence: 99%